Quantification of evolving moisture profiles in concrete samples subjected to temperature gradient by means of rapid neutron tomography: Influence of boundary conditions, hygro‐thermal loading history and spalling mitigation additives. (11th October 2020) - Tengattini, A.; Dal Pont, S.; Cheikh Sleiman, H.; Kisuka, F.; Briffaut, M.
Abstract: Concrete has a tendency to spall, that is, to eject layers when subjected to high temperatures. This is an erratic phenomenon, and our understanding of the underlying physical process is still limited. A driving process is moisture transfer, whose experimental investigation has so far mostly been limited to macroscopic or point‐wise observations, limiting both our understanding and the validation of the proposed models. In this paper, a non‐contact technique, neutron imaging, is used to extract a the full‐field distribution of moisture in 3D and in real time, while the concrete is heated at high temperatures. This reveals a number of processes often underestimated or ignored in the traditional experimental approaches reported in the literature. Notably, the effect on the evolving moisture profiles of varying heating rates for multiple insulation techniques as well the strong influence of the addition of spalling‐mitigating additives is presented. The first ever example of neutron tomography of a spalled sample is also reported, and some preliminary analyses of the effect that moisture clog formation and heating rates have on it are revealed.